Validation of the return of spontaneous circulation after cardiac arrest (RACA) score in two different national territories. (January 2019) - Caputo, Maria Luce; Baldi, Enrico; Savastano, Simone; Burkart, Roman; Benvenuti, Claudio; Klersy, Catherine; Cianella, Roberto; Anselmi, Luciano; Moccetti, Tiziano; Mauri, Romano; De Ferrari, Gaetano M.; Auricchio, Angelo
Abstract: Background: The likelihood of return of spontaneous circulation (ROSC) after out-of-hospital cardiac arrest (OHCA) is influenced by unmodifiable (gender, aetiology, location, the presence of witnesses and initial rhythm) and modifiable factors (bystander CPR and the time to EMS arrival). All of these have been included in the ROSC After Cardiac Arrest (RACA) score. Purpose: To test the ability of the RACA score to predict the probability of ROSC in two different regions with different local resuscitation networks: the Swiss Canton Ticino and the Italian Province of Pavia. Methods and Results: All OHCAs occurred between January 1 st 2015 and December 31 st 2017 were included. The original regression coefficients for all RACA score variables were applied. The probability to obtain the ROSC as measured with the RACA score was divided in tertiles. Overall, 2041 OHCAs were included in the analysis. The RACA score showed good discrimination for ROSC (AUC 0.76) and calibration, without interaction (p 0.28) between the region and the probability of ROSC. The probability of ROSC was 15% for RACA scores <0.28, 20% for RACA scores between 0.28 and 0.42, increasing to 55% for RACA scores >0.42. Conclusions: The application of the RACA score reliably assess the probability to obtain the ROSC, with equal effectiveness in the two regions, despite different organization of the resuscitation network. Patients with a RACA score >0.42 had more than 50% probability to obtain ROSC.